DOUBLE AND JOINT DEGREE PROGRAMS IN UKRAINE: REALIAS AND PROSPECTS - Olga Lysak (National Technical University of Ukraine "Kyiv Polytechnic Institute", 2017)
During the last ten years, with the adoption of legislation to promote academic mobility in Ukraine, the interest towards double/joint degree programs has increased dramatically. However, very little empirical research has been carried out to analyse the spread of the programs across Ukrainian universities and to outline the way such programs are used in particular educational institutions. The aim of this study was, therefore, to investigate the level of development of double/joint degree programs in Ukraine, analyse these programs according to the field of study and academic level. The main issues addressed in this article are special aspects, opportunities and issues connected with double and joint degrees. It is apparent that most double degree programs are offered in the areas of economics and management, while there are much fewer programs in the area of business. Double degree programs in economics, management and business tend to be fewer in number than non-degree mobility programs. The most common partner countries for establishing double degree programs are Poland, France, Italy, Slovakia, Sweden, the Netherlands, Austria, Spain and Lithuania. Sustainability of each program can be reached by permanent work on its improvement which includes making clear requirements, promotion of a program, increasing awareness on the benefits of studying abroad.